2021
DOI: 10.3390/s21248388
|View full text |Cite
|
Sign up to set email alerts
|

VestAid: A Tablet-Based Technology for Objective Exercise Monitoring in Vestibular Rehabilitation

Abstract: (1) Background: Current vestibular rehabilitation therapy is an exercise-based approach aimed at promoting gaze stability, habituating symptoms, and improving balance and walking in patients with mild traumatic brain injury (mTBI). A major component of these exercises is the adaptation of the vestibulo-ocular reflex (VOR) and habituation training. Due to acute injury, the gain of the VOR is usually reduced, resulting in eye movement velocity that is less than head movement velocity. There is a higher chance fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A large proportion reported that they would have benefited from additional telephone support, as it made them feel more motivated and adherent to exercise and helped build a therapeutic relationship with their therapist. To date, further platforms for the rehabilitation of vestibular disorders are emerging: information on tools still in the initial stage of experimentation can be retrieved from gray literature, such as WeBaVer and RehaMetrics ® , a [83] Norwegian platform created by Molde Hospital [84] and VestAid [85].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion reported that they would have benefited from additional telephone support, as it made them feel more motivated and adherent to exercise and helped build a therapeutic relationship with their therapist. To date, further platforms for the rehabilitation of vestibular disorders are emerging: information on tools still in the initial stage of experimentation can be retrieved from gray literature, such as WeBaVer and RehaMetrics ® , a [83] Norwegian platform created by Molde Hospital [84] and VestAid [85].…”
Section: Discussionmentioning
confidence: 99%
“…The VestAid records eye gaze stability ( Hovareshti et al., 2021 ). Patient X's eye gaze stability percentage improved from a median of 43% accuracy to 67% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…His plan of care included use of the VestAid tablet app. The VestAid tablet app can record eye/gaze compliance and head speed accuracy while performing the VOR x 1 exercise designed to create retinal slip, which drives an increase in the VOR gain ( Hovareshti et al., 2021 ; Hall et al., 2022 ; Schubert et al., 2008 ). VestAid uses eyes and facial recognition software to record the percentage of time that the patient kept their eyes on the target (eye gaze compliance accuracy).…”
Section: Case Presentationmentioning
confidence: 99%
“…VestAid is an innovative tablet-based system for vestibulo-ocular reflex exercises [ 32 ]. VestAid validated eye-gaze accuracy as part of the study and detected eye movement abnormalities in the participants with directed energy exposure, concussion, and vestibular neuritis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%